Effect of the Preheating Inlet Air on the G222 Fuel Combustion - Mohammed El Hadi Attia; Zied Driss; Abderrahmane Khechekhouche (International Journal of Energetica)
In this paper, a numerical simulation is developed to study the preheating effect of the air in a three-dimensional cylindrical combustion chamber using the FLUENT-CFD code. Particularly, we are interested on the calculation of the characteristic parameters such as the axial velocity, the temperature and the mass fraction of carbon monoxide. This study consists of a special treatment of mathematical models. The considered approaches resolve the governing equations of system. The main objective of this work is to study the behavior of the parameters considered previously during the variation of the air inlet temperature. The obtained results show that the variation of the inlet temperature presents a direct effect on the considered parameters.